Evaluation of skills transfer in short-term phacoemulsification surgery training program by International Council of Ophthalmology -Ophthalmology Surgical Competency Assessment Rubrics (ICO-OSCAR) and assessment of efficacy of ICO-OSCAR for objective evaluation of skills transfer - Bharucha, Khurshed M (Indian J Ophthalmol, 2020)
PURPOSE: To evaluate skills transfer in short-term phacoemulsification surgery training program by International Council of Ophthalmology -Ophthalmology Surgical Competency Assessment Rubrics (ICO-OSCAR) and assessment of efficacy of ICO-OSCAR for objective evaluation of skills transfer. METHODS: Prospective analysis of total 1300 phacoemulsification surgeries performed by 52 phacoemulsification trainees divided into three groups based on the previous cataract surgical experience. The pretraining and posttraining average mean scores, independent completion rates (ICR), and complication rates among the groups were calculated and statistically analyzed. RESULTS: Mean age of trainees (N = 52) was found to be 30.98 ± 2.44 years. Mean pretraining scores in the three groups were 42.8 ± 0.2, 46.6 ± 0.2, and 50.1 ± 0.1, respectively, and posttraining mean scores of the groups were 88.4 ± 0.2, 92.3 ± 0.2, and 94.3 ± 0.2, respectively, out of 100. Pretraining independent completion rates (%) were 22.1 ± 2.5, 52.1 ± 2.5, and 62 ± 3.7, respectively, and posttraining independent completion rates (%) were 74.8 ± 3, 79.7 ± 3, and 90.6 ± 3.5, respectively. Learning curves of all groups were noted to be steep. Rate of complications was within acceptable range, overall complication rate being 12.30% (160 out of 1300 cases). OSCAR scores correlate significantly (P = 0.0004) with ICR. CONCLUSION: Steep learning curve for phacoemulsification can be made easy by the use of standardized rubrics, proper techniques, expert guidance, and adequate surgical volume. The previous SICS experience provides smoother learning curve. ICO-OSCAR is indicator of proficiency and provides constructive feedback and objective evaluation immediately after surgery as well as at the end of training. Short-term (1 Month) training program is an effective, efficient, and safe approach to progressively master phacoemulsification skills for trainees with SICS experience.